Palladium Activated Decoration of TiO2 Nanotubes by Copper Nanoparticles and Enhanced Photocatalytic Properties - Liu, Ning; Jha, Himendra; Hahn, Robert; Schmuki, Patrik (ECS Electrochemistry Letters, 2012)
The present work describes how a simple two step activation/deposition process can be used to uniformly decorate TiO2 nanotube layers with suitable nanoparticles. In a first step Pd-activation is used to create initiation sites for a subsequent chemical deposition, in our example, Cu. We show that the procedure for two different nanotube types, when optimized, can yield very homogeneous particle decoration of the tube walls down to the bottom of the nanotubes. In the present case deposition and air exposure lead to mixed Cu/Cu-oxide decoration. We illustrate that this combination can be used for effective visible light photocatalysis.
EAM Import::2019-03-08